Analisis Pertimbangan Hakim dalam Memutus Perkara Pemberian Hibah yang Ditarik Kembali (Studi Putusan Nomor: 33/Pdt.G/2019/PN/PMS) - Gultom, Nurhayati; Tjempaka, Tjempaka (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This research was conducted with the aim of exploring the rights and obligations of grantors in revoking a grant, the legal impact on grant recipients who experience grant revocation, and analyzing the compatibility of Decision No. 33/Pdt.G/2019/PN.Pms of the Pematangsiantar District Court with the prevailing laws and regulations. This research used a normative legal approach and was descriptive in nature. The data collection methods used were library research and document analysis. Data analysis was conducted using qualitative analysis methods. The results of the research indicate that grantors have several rights based on Article 1669, Article 1671, and Article 1672 of the Civil Code and Article 212 of the Islamic Inheritance Law (KHI). Grantors also have the right to revoke their grant if the grant recipient fails to fulfill the obligations stipulated in the grant deed or other conditions specified in Article 1688 of the Civil Code. The legal impact on grant recipients who experience grant revocation is the return of the granted object to its original state before the agreement was made, as regulated by Article 1691 of the Civil Code. However, according to Article 212 of the KHI, a grant cannot be revoked, except in the case of a grant from a parent to their child, and this must be supported by a legally binding court decision. Based on the analysis of Decision No. 33/Pdt.G/2019/PN.Pms of the Pematangsiantar District Court, it can be concluded that the decision is in accordance with the prevailing laws and regulations.